Perbandingan Kinerja Reksadana Syariah Di Indonesia Menggunakan Metode SHARPE (Studi Kasus Reksadana Syariah Saham, Reksadana Syariah Pendapatan Tetap dan Reksadana Syariah Campuran periode 2012-2014) - Bintang Pratama Buana Putra; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research aims to find out the comparison between the performance of Islamic mutual funds of stock, Islamic mutual funds of fixed income and combined Islamic mutual funds. The method of this measuring calculates upon the risk factors and the return rate of those three kinds of Islamic mutual fund. This research uses 21 samples of Islamic mutual fund in Indonesia which consist of seven Islamic mutual funds of stock, seven Islamic mutual funds of fixed income and seven combined Islamic mutual funds. The approach used is a quantitative approach with the analysis technique of ANOVA. The result of this study shows that there is no difference between the performances of Islamic mutual funds of stock, Islamic mutual funds of fixed income and combined Islamic mutual funds on the period of January 2012 until December 2014 which has been analyzed using Sharpe method.